A study on hematological and immunological profile of patients with systemic Lupus Erythematosus - Dr. Akshatha. N; Dr. Shwetha Patil (Tropical Journal of Pathology and Microbiology, 2019)
Background: Systemic lupus erythematosus (SLE) is a chronic, relapsing, inflammatory and often febrile multisystem disorder of the connective tissue, characterized principally by involvement of the skin, joints, kidneys, and serosal membranes. Hematological findings may be present at the onset of the disease or can develop during the course of the disease. Since blood and blood vessels together contain more diverse number of antigens than any other organ in the body, it is only natural to expect hematological manifestations more often than the other systems.Objectives: To study the haematological and immunological Profile of Patients with Systemic Lupus Erythematosis.Methodology: An Ambispective study was conducted at Kasturba Medical College and hospital, Manipal from January 2011 to December 2013. A total of One hundred twenty seven cases of SLE were classified as having SLE according to the revised American College of Rheumatology (ACR) classification criteria (1997).Results: Hematological manifestations were frequently seen in the cases studied, which included anemia, neutropenia, lymphopenia, thrombocytopenia, pancytopenia, increased Erythrocyte sedimentation rate (ESR), presence of spherocytes, DCT positivity etc.Anemia was the most common hematological abnormality observed in the patients accounting to 87.4% (111/127) of cases. Hemoglobin of patients varied from a minimum of 3.8g/dl up to 13.5g/dl (Median = 9.6±2.2). The erythrocyte sedimentation rate (ESR) was assessed in all except one.The PCNA (Anti proliferating cell nuclear antigen) antibodies were positive in 44% of the cases.Conclusion: Hematological abnormalities are the commonest among all other anifestations in SLE, and their treatment is challenging. Bone marrow examination should be considered in all cases of severe or persistent leukopenia or thrombocytopenia in SLE, to exclude dug-induced myelotoxicity in susceptible patients.